2014
DOI: 10.1111/cen.12512
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of kisspeptin‐54 administration on GH, prolactin and TSH secretion in healthy women

Abstract: Summary Background The peptide hormone kisspeptin is essential for human reproduction, acting on the hypothalamus to stimulate gonadotrophin‐releasing hormone (GnRH) secretion. Kisspeptin is currently being evaluated as a novel therapeutic for women with infertility. However, some animal studies suggest that kisspeptin may also stimulate growth hormone (GH), prolactin and thyroid‐stimulating hormone (TSH) secretion, with implications for its safety; no previous study has investigated whether kisspeptin stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
(61 reference statements)
1
14
0
2
Order By: Relevance
“…In our study, we found no effect of administration of kisspeptin into the LV on GH secretion in intact ewes, which is in agreement with the reported lack of response to peripheral administration in intact cows studies (Whitlock et al 2008) and prepubertal female pigs (Lents et al 2008) but contrasts with a small GH increase reported in ewes (Whitlock et al 2010) although the immediate nutritional status may be key in this model (Foradori et al 2017). In women, both acute and chronic peripheral administration of kisspeptin-54 failed to alter GH concentrations (Jayasena et al 2014). As mentioned above, these varying and contradictory reports on the effects of kisspeptin on GH may be the result of cross signalling through the large family of RFamide receptors, especially when high doses are administered centrally.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we found no effect of administration of kisspeptin into the LV on GH secretion in intact ewes, which is in agreement with the reported lack of response to peripheral administration in intact cows studies (Whitlock et al 2008) and prepubertal female pigs (Lents et al 2008) but contrasts with a small GH increase reported in ewes (Whitlock et al 2010) although the immediate nutritional status may be key in this model (Foradori et al 2017). In women, both acute and chronic peripheral administration of kisspeptin-54 failed to alter GH concentrations (Jayasena et al 2014). As mentioned above, these varying and contradictory reports on the effects of kisspeptin on GH may be the result of cross signalling through the large family of RFamide receptors, especially when high doses are administered centrally.…”
Section: Discussionsupporting
confidence: 90%
“…Kisspeptin stimulated calcium influx in rat somatrotropes and secretion of GH from rat (Gutierrez-Pascual et al 2007) and bovine (Kadokawa et al 2007) pituitary cells. However, Jayasena et al (2014) found no effect of kisspeptin on GH secretion from the pituitary in vitro. In vivo studies present a complexity of findings including contradictory reports.…”
Section: Discussionmentioning
confidence: 87%
“…Administration of kisspeptin-10 to culture media prepared with anterior pituitary cells extracted from 8-month-old castrated male calves increased prolactin secretion (49). However, several other studies were unable to demonstrate such effect (Table 1) (50)(51)(52)(53). In humans, for example, acute or a week of twice-daily subcutaneous (sc) administrations of kisspeptin-54, at a dose known to stimulate gonadotropin secretion, induced no effect on serum prolactin levels in healthy women (53).…”
Section: Interaction Between Prolactin and The Kisspeptin Systemmentioning
confidence: 98%
“…However, several other studies were unable to demonstrate such effect (Table 1) (50)(51)(52)(53). In humans, for example, acute or a week of twice-daily subcutaneous (sc) administrations of kisspeptin-54, at a dose known to stimulate gonadotropin secretion, induced no effect on serum prolactin levels in healthy women (53). In fact, the ability of kisspeptin to induce prolactin secretion seems to be directly related to circulating estrogen levels, as demonstrated in rodents.…”
Section: Interaction Between Prolactin and The Kisspeptin Systemmentioning
confidence: 99%
“…139 In line with these negative findings, systemic treatments with kisspeptins have been reported to cause no change in prolactin secretion in the sheep, 143 goat, 144 monkey, 145 and women. 146 There appears, therefore, that kisspeptin is not able to stimulate prolactin secretion directly from the lactotrophs in the majority of species investigated so far. It is also unclear how kisspeptin would reach the pituitary gland in significant concentrations, as this is not likely from the known neuronal populations in the hypothalamus.…”
Section: Kisspeptin Effects On Prolactin At the Pituitary Levelmentioning
confidence: 95%